Emergence of novel reassortant H3N2 swine influenza viruses with the 2009 pandemic H1N1 genes in the United States - Liu, Qinfang; Ma, Jingjiao; Liu, Haixia; Qi, Wenbao; Anderson, Joe; Henry, Steven C.; Hesse, Richard A.; Richt, Juergen A.; Ma, Wenjun (My University, 2011)
Reassortant H1 swine influenza viruses (SIVs) carrying 2009 pandemic H1N1 virus (pH1N1) genes have been isolated from pigs worldwide. Seven novel reassortant H3N2 SIVs were identified from diseased pigs in the USA from winter 2010 to spring 2011. These novel viruses contain three or five internal genes from pH1N1 and continue to circulate in swine herds. The emergence of novel reassortant H3N2 SIVs demonstrates reassortment between pH1N1 and endemic SIVs in pigs and justifies continuous surveillance.
Keywords: Reassortment; Pandemic H1N1; H3N2 swine influenza virus